Sonographic imaging of fetal tympanic rings. (9th October 2013) - Leibovitz, Z.; Egenburg, S.; Bronshtein, M.; Shapiro, I.; Tepper, R.; Malinger, G.; Ohel, G.
ABSTRACT: Objective: To examine the feasibility of ultrasonographic imaging of fetal tympanic rings . Methods: This was an observational cohort study of 80 healthy fetuses in low‐risk pregnancies, divided into four gestational‐age subgroups (12, 16, 23 and 32 weeks), each comprising 20 consecutive fetuses. Tympanic ring visualization was achieved by two‐dimensional and three‐dimensional (3D) sonography. A standard algorithm for tympanic ring examination was constructed using 3D multiplanar reconstruction. The volume acquisition plane was directed to the inferolateral aspect of the fetal temporal bone. Transvaginal scans were carried out in the 12‐week and 16‐week subgroups, and transabdominal scans in the 23‐week and 32‐week subgroups. Study parameters included the inferomedial inclination angle (IMIA) of the tympanic ring relative to the vertical skull axis, the anteromedial inclination angle (AMIA) of the tympanic ring relative to the anteroposterior skull axis and the longest (LTRD) and shortest (STRD) tympanic ring diameter, the latter measured perpendicular to the LTRD. The feasibility of tympanic ring demonstration was assessed in each gestational‐age subgroup . Results: Tympanic rings appeared as round‐oval, thin, echogenic structures in a plane tangential to the inferolateral surface of the fetal skull below the inferior border of the squamous part of the temporal bone. Higher demonstration rates were achieved in the 16‐week and 23‐week subgroups (90% and 80%, respectively) than in the others. LTRD and STRD each showed a linear correlation with gestational age ( r  = 0.96 for both measurements ; P  < 0.01). Mean IMIA ranged from 41.0 to 60.4° and mean AMIA from 17.3 to 23.4° across the different gestational‐age subgroups. The malleal manubrium was observed only in examinations in the second half of pregnancy, appearing as a bright echo within the upper area of the tympanic ring in 56% (9/16) and 82% (9/11) of cases with tympanic ring imaging appropriate for measurement of the study parameters in the 23‐week and 32‐week subgroups, respectively . Conclusion: This is the first report of sonographic imaging of fetal tympanic rings and shows that this is feasible in the second trimester. We discuss the possible implications of our findings for the prenatal diagnosis of congenital hearing loss. Copyright © 2013 ISUOG. Published by John Wiley & Sons Ltd .